Apparent Aortic Stiffness in Children With Pulmonary Arterial Hypertension: Existence of Vascular Interdependency?. (February 2017) - Schäfer, Michal; Ivy, D. Dunbar; Abman, Steven H.; Barker, Alex J.; Browne, Lorna P.; Fonseca, Brian; Kheyfets, Vitaly; Hunter, Kendall S.; Truong, Uyen
Abstract : Background—: Left ventricular dysfunction, mediated by ventricular interdependence, has been associated with negative outcomes in children with pulmonary arterial hypertension (PAH). Considering the dilation of the pulmonary arteries as a paramount sign of PAH, we hypothesized that the ascending aorta will present signs of apparent stiffness in children with PAH and that this effect may be because of mechanical interaction with the dilated main pulmonary artery (MPA). Methods and Results—: Forty-two children with PAH and 26 age- and size-matched controls underwent comprehensive cardiac magnetic resonance evaluation. Assessment of aortic stiffness was evaluated by measuring pulse wave velocity, aortic strain, and distensibility. Children with PAH had significantly increased pulse wave velocity in the ascending aorta (3.4 versus 2.3 m/s for PAH and controls, respectively; P =0.001) and reduced aortic strain (23% versus 29%; P <0.0001) and distensibility (0.47 versus 0.64%/mm Hg; P =0.02). Indexed MPA diameter correlated with pulse wave velocity ( P =0.04) and with aortic strain ( P =0.02). The ratio of MPA to aortic size correlated with pulse wave velocity ( P =0.0098), strain ( P =0.0099), and distensibility ( P =0.015). Furthermore, aortic relative area change was associated with left ventricular ejection fraction ( P =0.045) and ventricular–vascular coupling ratio ( P =0.042). Conclusions—: Pediatric PAH patients have increased apparent ascending aortic stiffness, which was strongly associated with the degree of MPA distension. We speculate that distension of the MPA may play a major role in limiting full aortic expansion during systole, which modulates left ventricular performance and impacts systemic hemodynamics in pediatric PAH. Abstract : Supplemental Digital Content is available in the text.